2021
DOI: 10.2196/24320
|View full text |Cite
|
Sign up to set email alerts
|

Jobs, Housing, and Mask Wearing: Cross-Sectional Study of Risk Factors for COVID-19

Abstract: Background Many studies have focused on the characteristics of symptomatic patients with COVID-19 and clinical risk factors. This study reports the prevalence of COVID-19 in an asymptomatic population of a hospital service area (HSA) and identifies factors that affect exposure to the virus. Objective The aim of this study is to measure the prevalence of COVID-19 in an HSA, identify factors that may increase or decrease the risk of infection, and analyze… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 25 publications
3
17
0
Order By: Relevance
“…Furthermore, we know that SARS-CoV-2 can remain airborne for up to three hours and survive on surfaces [ 17 ]. In agreement with previous studies [ 18 , 19 ], we observed that participants living in houses were at a lower risk of infection than were participants living in apartments. It can be hypothesized that single-family homes allow more frequent access to the outdoors than do apartments.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, we know that SARS-CoV-2 can remain airborne for up to three hours and survive on surfaces [ 17 ]. In agreement with previous studies [ 18 , 19 ], we observed that participants living in houses were at a lower risk of infection than were participants living in apartments. It can be hypothesized that single-family homes allow more frequent access to the outdoors than do apartments.…”
Section: Discussionsupporting
confidence: 93%
“…People who live in larger cities and individuals with higher education, especially women, had a lower risk of infection, which is in agreement with published data 20 . Household size, and in men especially the number of children under 20 years of age, was associated with a higher risk of infection, which again agrees with published data 3,4 . People living on their own had a much lower risk of infection than those who share household with someone else and singles also reported a less severe course of Covid-19.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, the range of factors examined by these retrospective or cross-sectional studies was rather limited. Factors significantly or non-significantly associated with Covid-19 were sex 1 , age 1 , ethnicity 2 , urbanisation 3 , residence in a multifamily unit 4 , BMI and obesity 2,5,6 , smoking 2,7 , physical fitness and forced expiratory volume 2 , the number of daily contacts 3 , wearing masks and washing hands 3 , socioeconomic deprivation 2 , particular AB0 blood groups [8-10], Rh factor [10], vitamin D deficiency [11], high-density lipoprotein level 2 , use of immunosuppressants 8 , and a growing set of comorbidities – cardiovascular disease, chronic obstructive pulmonary disease (COPD), chronic kidney disease, dementia, hypertension and functional dependence 6 , and toxoplasmosis 9 . Other factors, such as contact with animals, have been suggested only on a theoretical basis 10 or are merely discussed in non-scientific sources, such as popular literature or the internet.…”
Section: Introductionmentioning
confidence: 99%
“…For social determinants, we considered a limited set of measures previously shown to be associated with test-positivity; [33] and mechanistically drive transmission dynamics by considering frequency of contacts and who contacts whom. [34] These include: socio-demographic variables that are proxies of economic barriers and systemic racism (income;% visible minority;% recent immigration); dwelling-related variables (% suitable housing; [ 35 , 36 ]% multigenerational households); and occupation-related variables (% working in essential services [health; trades, transport and equipment operation; sales and services; manufacturing and utilities; resources, agriculture, and production]) [37] …”
Section: Methodsmentioning
confidence: 99%